Measuring leadership values based on value-based total performance excellence model (VBTPEM) / Mohd Rashid Ab Hamid , Zainol Mustafa , Nur Riza Mohd Suradi , Mokhtar Abdullah , Fazli Idris , Wan Rosmanira Ismail , Zalina Mohd Ali and Norkisme Zainal Abidin - Ab Hamid, Mohd Rashid; Mustafa, Zainol; Mohd Suradi, Nur Riza; Abdullah, Mokhtar; Idris, Fazli; Ismail, Wan Rosmanira; Mohd Ali, Zalina; Zainal Abidin, Norkisme (Institute of Business Excellence and UPENA, 2010)
This paper discussed the core values of leadership and its indicators based on the Value-Based Total Performance Excellence Model (VBTPEM) in the context of Institution of Higher Learning (IHL) i.e. the university. The pilot study was conducted at the selected university and produced high reliability index of Cronbach’s alpha (α = 0.866). Multivariate technique i.e. Structural Equation Modelling (SEM) was deployed for the analysis and resulted the GFI = 0.966, CFI = 0.991, and TLI = 0.980 while RMSEA is 0.067 with p = 0.07 and the data fit the model of the single-order measurement of leadership values model. In conclusion, the instrument for measuring the leadership values is suitable to be administered as it was tailored to needs and applicability at the Institutions of Higher Learning (IHL) in Malaysia.